English Students’ Attitudes toward the Implementation of Multiple Distanced-Learning Platforms during Covid-19 Outbreak - Fujiono Fujiono (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
This preliminary case study was to describe how the enactment of multiple distanced learning platform has impacts of students’ attitudes during the covid-19 outbreak. . The data were garnered from the zoom and whatApps mediated English learning in the university in Madura. The results indicate not only psychological but also hardskills of the English arose. The students felt their motivation to have online learning develop as well as their attitude toward their English learning. As immerging data are still limited in terms of coverage and still in on going interpretation and analysis, the students English skills become significant to investigate in the future. Studi kasus pendahuluan ini untuk mendeskripsikan bagaimana pemberlakuan platform pembelajaran jarak jauh ganda memiliki dampak terhadap sikap siswa selama wabah covid-19. . Data dikumpulkan dari zoom dan whatApps yang dimediasi pembelajaran bahasa Inggris di universitas di Madura. Hasil menunjukkan tidak hanya psikologis tetapi juga hardskills bahasa Inggris muncul. Para siswa merasakan motivasi mereka untuk mengembangkan pembelajaran online serta sikap mereka terhadap pembelajaran bahasa Inggris mereka. Karena data yang muncul masih terbatas dalam hal cakupan dan masih dalam interpretasi dan analisis yang sedang berlangsung, kemampuan bahasa Inggris siswa menjadi penting untuk diselidiki di masa depan.